2013
DOI: 10.1074/jbc.m112.394155
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Serum Amyloid A 1.1 Shows a Long Oligomer-rich Fibrillation Lag Phase Contrary to the Highly Amyloidogenic Non-pathogenic SAA2.2

Abstract: Background: Murine SAA1.1 is pathogenic and SAA2.2 is non-pathogenic in AA amyloidosis. Results: SAA1.1 and SAA2.2 exhibit different biophysical properties, including fibrillation kinetics and fibril morphology. Conclusion:The distinct biophysical properties of highly homologous SAA proteins may contribute to their different pathogenicity during chronic inflammation. Significance: Structural and kinetic factors, more than their intrinsic amyloidogenicity, may determine the diverse pathogenicity among nearly id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 48 publications
(60 reference statements)
3
49
0
Order By: Relevance
“…The refolded SAA1.1 has an apparent molecular mass of 43 kDa by size-exclusion chromatography (SEC), consistent with it being a trimer or tetramer (Fig. 3A) (20). Further analytical ultracentrifugation (AUC) experiments showed a sedimentation velocity (SV) profile of the refolded SAA1.1 consisting of monomers, trimers, and hexamers, with the majority being trimers at a concentration of ∼0.36 mg/mL but becoming monomers at lower concentrations (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The refolded SAA1.1 has an apparent molecular mass of 43 kDa by size-exclusion chromatography (SEC), consistent with it being a trimer or tetramer (Fig. 3A) (20). Further analytical ultracentrifugation (AUC) experiments showed a sedimentation velocity (SV) profile of the refolded SAA1.1 consisting of monomers, trimers, and hexamers, with the majority being trimers at a concentration of ∼0.36 mg/mL but becoming monomers at lower concentrations (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…3B). Unlike similar-size mSAA1 oligomers described in previous detailed studies (24), the pH 4.3 oligomers are distinct in their high structural stability (Fig. 1B) and affinity for A11 seen in the freshly dissolved SAA (Fig.…”
Section: Effects Of Ph On Saa Interactions With Phospholipids and Thementioning
confidence: 74%
“…38, 39 and references therein). Furthermore, compact soluble polymorphic low-order oligomers of various amyloidogenic proteins, including SAA (21)(22)(23)(24), are thought to comprise the pathogenic species that can disrupt cell membranes and/or mediate prion-like transmission (7,8,(13)(14)(15)40). Notably, studies of soluble low-order oligomeric forms of Aβ have revealed a direct correlation between the ANS binding and cytotoxicity (9), whereas studies of a model amyloidogenic protein HypF reported that "structural flexibility and hydrophobic exposure are primary determinants of the ability of oligomeric assemblies to cause cellular dysfunction" (13).…”
Section: Effects Of Ph On Saa Interactions With Phospholipids and Thementioning
confidence: 99%
See 1 more Smart Citation
“…For all forms of amyloidosis, soluble precursors exist, which may be synthesized locally or distributed systemically in forms of amyloid affecting multiple organs (1). For the systemic amyloidoses, the precursor-fibril conversion is only partially understood, progressing in some instances through oligomers with enhanced cytotoxic, oxidant, or apoptotic effects (2). In addition, clearance mechanisms exist for seemingly stable amyloid, as witnessed by the presence of surrounding macrophages and giant cells in some localized forms, clinical regression of systemic disease if the precursor protein is reduced or eliminated, or when amyloid is depleted immunologically (3).…”
mentioning
confidence: 99%